Arsenic Irradiation Induced Atomic Interdiffusion of InxGa1-xAs/InP Quantum Well Structures - P.L. Gareso; H.H. Tan; C. Jagadish (Atom Indonesia, 2012)
The atomic intermixing of InxGa1-xAs/InP quantum well structures induced by arsenic irradiation has been investigated using photoluminescence (PL) measurement. The ion doses used were varried from 5x1011 As/cm2 to 1x1013 As/cm2. Also, the irradiation temperature were carried out from -200oC to 300oC. The samples were annealed under Argon flow in rapid thermal annealer (RTA) at 750oC for 60 second. The photoluminescence result showed that there was increase in energy shift at lower doses. However, the energy shift was saturated at higher dose. At elevated temperature implantation showed that the energy shift did not change significantly for all the samples (LM, TS, CS). In additon to this, the higher energy shift was observed in the Compressive Strain (CS) samples, but the lower of the energy shift was experienced in the Tensile Strain (TS) samples. Received: 06 September 2012; Revised: 27 November 2012; Accepted: 03 December 2012